ATNX2 is not a regulatory gene in Italian ALS patients with C9ORF72 GGGGCC expansion - Chiò, Adriano (Neurobiol Aging, 2015)
There are indications that both familial ALS and sporadic ALS phenotype and prognosis are partly regulated by genetic and environmental factors, supporting the theory that ALS is a multifactorial disease. The aim of this paper was to assess the role of ATXN2 intermediate length repeats in a large series of Italian and Sardinian ALS patients and controls carrying a pathogenetic C9ORF72 GGGGCC hexanucleotide repeat. A total of 1972 ALS cases were identified through the database of the Italian ALS Genetic consortium (ITALSGEN), a collaborative effort including 18 ALS centers throughout Italy. The study population included: (1) 276 Italian and 57 Sardinian ALS cases who carried the C9ORF72 expansion; (2) 1340 Italian and 299 Sardinian ALS cases not carrying the C9ORF72 expansion. A total of healthy 1043 controls were also assessed. Most Italian and Sardinian cases and controls were homozygous for 22/22 or 23/23 repeats or heterozygous for 22/23 repeats of the ATXN2 gene. ATXN2 intermediate length repeats alleles (≥28) were detected in 3 (0.6%) Italian ALS cases carrying the C9ORF72 expansion, in none of the Sardinian ALS cases carrying the expansion, in 60 (4.3%) Italian cases not carrying the expansion, and in 6 (2.0%) Sardinian ALS cases without C9ORF72 expansion. Intermediate length repeat alleles were found in 12 (1.5%) Italian controls and 1 (0.84%) Sardinian controls. Therefore, ALS patients with C9ORF72 expansion showed a lower frequency of ATXN2 polyQ intermediate length repeats than both controls (Italian cases, p=0.137; Sardinian cases, p=0.0001) and ALS patients without C9ORF72 expansion (Italian cases, p=0.005; Sardinian cases, p=0.178). In our large study on Italian and Sardinian ALS patients with C9ORF72 GGGGCC hexanucleotide repeat expansion, compared to age-, gender- and ethnic-matched controls, ATXN2 polyQ intermediate length does not represent a modifier of ALS risk, differently from non-C9ORF72 mutated patients.